Potensi Metabolit Sekunder Isolat Aktinomycetes Sebagai Penghasil Senyawa Antibakteri Terhadap Methicillin Resistant Staphylococcus aureus (MRSA) Dari Tanah Mangrove Wonorejo Surabaya - Anita Dwi Anggraini; Ayu Puspitasari; Christ Kartika Rahayuningsih (Universitas Muhammadiyah Surabaya, 2021)
Infectious diseases are estimated to be the cause of half of all deaths worldwide. About 50-75% of deaths in hospital are reported to be due to infection. This number continues to increase rapidly in line with the development of bacterial resistance to certain antibiotics. One of the causes of resistance due to antibiotic abuse. The number of resistance events that occur encourages new discoveries in order to overcome the problem of resistance. Actinomycetes are Gram-positive microscopic bacteria that are widespread in nature. These bacteria can live in various environmental conditions that contain lots of nutrients. Actinomycetes population increases in the presence of organic matter that undergoes decomposition. Acinomycetes have the ability to produce antimicrobial compounds. The need for antibiotic compounds and chemotherapy compounds that are effective with low toxicity to the host, and the resulting waste can be degraded by the environment, is a problem that needs serious attention. The existence of resistance to antibiotics causes the need to develop new types of antibiotics from natural ingredients and microorganisms that can control microbapatogens. Compounds obtained from natural materials, especially plants and microbes, provide promising results in the development of new antibiotic compounds, among the existing types of microorganisms, Actinomycetes are the most potential source of producing antibiotics. Apart from antibiotics, actinomycetes also produce bioactive compounds of high economic value in the health sector as antiviral and anti-cancer, while in agriculture as herbicides, insecticides, and anti-parasitic compounds. This causes the need to explore actinomycetes which have the potential to produce antibiotic compounds against bacteria. This study aims to determine the antibacterial activity of secondary metabolites of actinomycetes isolates against cuts infected with Staphylococcus aureus resistant methicillin (MRSA) in winstar rats (rattus norvegicus). This type of research is carried out in an experimental laboratory. The results showed that the potential for secondary metabolites of actinomysetes isolates against MRSA bacteria was classified as strong with an inhibitory index of 10.1.